Pemanfaatan Aplikasi Wattpad Dalam Memotivasi Siswa Untuk Menulis Cerita - Ria Ananda Putri (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
Social media is a online media, with the users can easily participate, share, and created the blog, covering social network, wiki, forum and virtual world. Now, many one who uses social media especially teenagers. Teenager in indonesia often takes social media to channel their creativity. One of them is from writing. Inordinate social media that can be used to channel from writing. Research methodology used the research is research methodology qualitative, interpret how the role the application wattpad in motivate students for writing a story is a data collection. he result of research that is done in minutely student average by researchers , in general have motivation and desire to write wattpad applications .Although some of them have not dare do it with reason lacking in confidence .But , there are face the its position not only as the reader , will also active as a writer to keep writing motivated and be able to .